Age-specific effects of ozone on pneumonia in Korean children and adolescents: a nationwide time-series study - Kim, Kyoung Nam; Lim, Youn Hee; Bae, Sanghyuk; Song, In Gyu; Kim, Soontae; Hong, Yun Chul (Epidemiology and Health, 2022)
OBJECTIVES: The aim of this study was to estimate the age-specific effects of 8-hour maximum ozone levels on pneumonia in children and adolescents. METHODS: We performed quasi-Poisson regression analyses for individuals of 0-4 years, 5-9 years, 10-14 years, and 15-19 years of age using nationwide time-series data from the Korea (2011-2015). We constructed distributed lag linear models employing a generalized difference-in-differences method and controlling for other air pollutants. RESULTS: A 10.0-parts per billion increase in 8-hour maximum ozone levels was associated with a higher risk of hospital admissions due to pneumonia at 0-4 (relative risk [RR], 1.02; 95% confidence interval [CI], 1.01 to 1.03) and 5-9 years of age (RR, 1.06; 95% CI, 1.04 to 1.08), but not at 10-14 (RR, 1.01; 95% CI, 0.98 to 1.04) or 15-19 years of age (RR, 1.01; 95% CI, 0.97 to 1.06). The association between ozone and hospital admissions due to pneumonia was stronger in cool seasons (from November to April) than in warm seasons (from May to October), but was similar between boys and girls. CONCLUSIONS: Short-term exposure to ozone was associated with a higher risk of pneumonia at 0-4 years and 5-9 years of age, but not at 10-14 years or 15-19 years of age. Our findings can help identify vulnerable periods, determine the target populations for public health interventions, and establish air pollution standards.
Keywords: Adolescent; Age Factors; Air Pollutants; Air Pollution; Child; Female; Humans; Male; Ozone; Pneumonia; Seasons; Adolescent; Children; Ozone; Pneumonia; Time-series analysis